Outcome of intraoperative use of mitomycin C combined with conjunctival auto graft in recurrent pterygium - MK Goswami; F Hossain; AB Shamsudduha; M Asaduzzaman (IMC Journal of Medical Science, 2016)
Background and objectives: Recurrent pterygium is an important ocular problem in our country. There are different modalities of treatment for recurrent pterygium. The present study was undertaken to determine the effect of intraoperative mitomycin C along with conjunctival auto graft to prevent recurrence of pterygium.